Established and emerging GABAA receptor pharmacotherapy for epilepsy - Richardson, Robert J.; Petrou, Steven; Bryson, Alexander (Frontiers in Pharmacology, 2024)
Gamma-aminobutyric acid (GABA) is the principal inhibitory neurotransmitter in the mammalian brain and one of the central pathways through which it modulates the excitability of neural circuits is through the GABAA receptor. Impairments of GABAA receptor inhibition leads to excitation-inhibition imbalance and can predispose to epilepsy, and enhancing GABAA receptor activity has been a mainstay of acute and chronic antiseizure therapy for over a century. The last decade has seen renewed interest in novel agents that precisely target subpopulations of GABAA receptors that exert differing influence over neural circuit function, as well as opportunities for the repurposing of older drugs for different disease indications. This article will provide an up-to-date review of both established agents that form a central part of the antiseizure pharmacological armamentarium, and emerging drugs whose role in the clinical management of epilepsy is yet to be finalised.